Determinants of sustainable continuous improvement (Kaizen) implementation in Malaysian automotive part supplier SMEs - Mohd Ghazali, Maarof; Sorooshian, Shahryar; Suhaila, Abdul Hamid (IEOM Society International, 2018)
Globalization has caused many organizations to adapt themselves to the ever-changing business environment in order to sustain in this competitive market condition. Malaysian automotive part suppliers SMEs are also affected by the globalization. To remain competitive in this challenging business environments, the SMEs need to ensure continuous improvement are being implemented as part of their business strategy. This paper presents findings from a larger study on Kaizen implementation among automotive part supplier SMEs in Malaysia. Nine semi-structured interviews were conducted with four automotive part supplier SMEs located in Selangor and Pahang. The data during the interview were recorded, transcribed and coded before being divided according to relevant themes. Top management commitment, training, kaizen champion, supportive organization culture, communication, recognition and reward and employee empowerment are found to be among the determinants for successful continuous improvement. The findings from this study are useful to help companies to embark or sustain their kaizen activities. Furthermore, it is useful information to respective government agencies to develop policies that can help Malaysian automotive industry especially the SMEs to sustain their business.